Computing science, communication and security : first International Conference, COMS2 2020, Gujarat, India, March 26-27, 2020, Revised selected papers /: first International Conference, COMS2 2020, Gujarat, India, March 26-27, 2020, Revised selected papers. (2020) - Unknown
No abstract available